2011
DOI: 10.1109/tbme.2011.2126572
|View full text |Cite
|
Sign up to set email alerts
|

A Portable Image Overlay Projection Device for Computer-Aided Open Liver Surgery

Abstract: Image overlay projection is a form of augmented reality that allows surgeons to view underlying anatomical structures directly on the patient surface. It improves intuitiveness of computer-aided surgery by removing the need for sight diversion between the patient and a display screen and has been reported to assist in 3-D understanding of anatomical structures and the identification of target and critical structures. Challenges in the development of image overlay technologies for surgery remain in the projecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 18 publications
1
70
0
Order By: Relevance
“…This instrument is currently undergoing clinical trials and we have employed this procedure to ensure sterility of the instrument. As an alternative solution, the concept of a projection-based tracking pod used in surgical navigation systems 24 is expected to be explored in our future research.…”
Section: Discussionmentioning
confidence: 99%
“…This instrument is currently undergoing clinical trials and we have employed this procedure to ensure sterility of the instrument. As an alternative solution, the concept of a projection-based tracking pod used in surgical navigation systems 24 is expected to be explored in our future research.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed solution can be the theoretic basis of more practical applications [1], [2]. For example, an interesting future work will be planning multiple projectors to cover a complex indoor area.…”
Section: Discussionmentioning
confidence: 99%
“…It is a fundamental problem in spatial augmented reality [1] and projector-camera systems [2] in which the primary display device is a video projector.…”
Section: Introductionmentioning
confidence: 99%
“…As the image overlay device relies on the registration and tracking capabilities of the navigation system into which it is integrated, the accuracy of the device also depends on the accuracy of the navigation system. In a previous study [14], the image overlay device was found to have a mean projection accuracy of 1.3 mm when integrated into a Liver Surgical Navigation System [16] with navigation camera accuracy of approximately 0.3 mm. Tests were performed on both planar and 3D rigid models.…”
Section: Image Overlay Projectionmentioning
confidence: 96%
“…A portable projection image overlay device (IOD) [14] developed within our institute displays medical data directly on the patient and overcomes many of the deficiencies of previously described AR approaches. The device is minimally intrusive, non-impeding to the view of the surgeon, and efficient in set-up and movement handling.…”
Section: Introductionmentioning
confidence: 99%